Assessment of retroviral activity using a universal retrovirus chip - Seifarth, Wolfgang; Spiess, Birgit; Zeilfelder, Udo; Speth, Cornelia; Hehlmann, Rüdiger; Leib-Mösch, Christine (Journal of virological methods, 2003)
A DNA chip-based assay is described for parallel detection and identification of a wide variety of human and mammalian exogenous and endogenous retroviruses. The assay combines multiplex polymerase chain reaction (PCR) using fluorochrome-modified primer mixtures and chip hybridization. The microarray is composed of retrovirus-specific synthetic oligonucleotides as capture probes deposited on glass slides. The retrovirus chip can be used to assess the occurrence of reverse transcriptase (RT)-related transcripts in biological samples of human and mammalian origin. For example, distinct expression profiles of human endogenous retroviruses (HERV) were established reproducibly in human white blood cells, mammary gland and other human tissues. In particles released by human cells, packaging of specific HERV transcripts could be observed. Monitoring of human exogenous retroviruses (HIV, HTLV) and detection of putative cross-species transmissions (MLV, PERV) in human samples was efficient and reliable. The DNA chip should be an excellent tool for the detection of most relevant retroviruses and offers insights into differential retroviral activities and replication strategies. Furthermore, it could improve significantly the safety of gene therapy, tissue engineering, xenotransplantation and production of therapeutic polypeptides in cell culture.
Gesehen am 12.05.2022